2021
DOI: 10.1186/s12940-021-00735-w
|View full text |Cite
|
Sign up to set email alerts
|

Time-series analysis of daily ambient temperature and emergency department visits in five US cities with a comparison of exposure metrics derived from 1-km meteorology products

Abstract: Background Ambient temperature observations from single monitoring stations (usually located at the major international airport serving a city) are routinely used to estimate heat exposures in epidemiologic studies. This method of exposure assessment does not account for potential spatial variability in ambient temperature. In environmental health research, there is increasing interest in utilizing spatially-resolved exposure estimates to minimize exposure measurement error. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 43 publications
0
11
0
1
Order By: Relevance
“…The analyses were based on hospitalisations (i.e., each hospitalisation as one case) and one patient could have had one or multiple hospitalisations. Because the existing epidemiological studies 29 , 30 and our previous studies 31 , 32 suggested that ambient heat exposure is not only associated with morbidity on the same day of exposure but also one to two days after exposure, we used a distributed lag non-linear model to capture the association lasting from the current day of exposure to two days after exposure (i.e., lag 0–2 days). We used a natural cubic spline with three degrees of freedom for the mean temperature to capture the potential non-linear relationship between mean temperature and hospitalisations.…”
Section: Methodsmentioning
confidence: 99%
“…The analyses were based on hospitalisations (i.e., each hospitalisation as one case) and one patient could have had one or multiple hospitalisations. Because the existing epidemiological studies 29 , 30 and our previous studies 31 , 32 suggested that ambient heat exposure is not only associated with morbidity on the same day of exposure but also one to two days after exposure, we used a distributed lag non-linear model to capture the association lasting from the current day of exposure to two days after exposure (i.e., lag 0–2 days). We used a natural cubic spline with three degrees of freedom for the mean temperature to capture the potential non-linear relationship between mean temperature and hospitalisations.…”
Section: Methodsmentioning
confidence: 99%
“…We acquired patient-level ED visit data as part of the Environmental Exposures and Health Across the Nation (ENVISION) study. 20 , 36 The ENVISION database includes outpatient and inpatient billing records from individual states, with key variables for each patient record including date of visit, whether the visit resulted in an admission to the hospital (ED admission), International Classification of Disease Ninth Revision (ICD-9) diagnosis codes, patient age, and ZIP code of patient residence.…”
Section: Methodsmentioning
confidence: 99%
“…Meteorological data on daily maximum air temperature and mean dew-point temperature were obtained from the weather station at the Hartsfield–Jackson Atlanta International Airport, which was close to the urban center of the Atlanta metropolitan area. Thomas et al 37 compared the temperature measurements at the airport to the region-wide means of a well-known meteorology product (Daymet) in Atlanta and observed a high correlation between the two. For this analysis, we opted to use the airport measurements due to their high-quality, complete temporal coverage, and its central location in our study area with little variation in elevation.…”
Section: Methodsmentioning
confidence: 99%